Impact of coaptation gap location on procedural strategy and outcomes following tricuspid transcatheter edge-to-edge repair: insights from the TriClip bRIGHT study. (3rd October 2022) - Donal, E; Sitges, M; Panis, V; Schueler, R; Lapp, H; Moellmann, H; Nickenig, G; Bekeredjian, R; Estevez, R; Atmowihardjo, I; Trusty, P; Lurz, P
Abstract: Background: As tricuspid transcatheter edge-to-edge repair (TEER) gains momentum, a better understanding of coaptation gap size and location becomes increasingly important to properly select patients for this therapy. The tricuspid valve is complex and patient phenotypes may be highly variable. It is currently unknown how location of the coaptation gap may impact procedural strategy and clinical outcomes. Purpose: To characterize the coaptation gap in patients receiving tricuspid TEER and investigate the effect of coaptation gap location on procedural strategy and short-term outcomes. Methods: bRIGHT is a prospective, multi-center, single arm post-market study evaluating the safety and effectiveness of the TriClip device in symptomatic patients with severe tricuspid regurgitation. Detailed echocardiographic coaptation gap measurements were performed on 135 subjects (from 24 sites) with available echo. Procedural and short-term outcomes were stratified by coaptation gap location. Results: The biplane RV inflow/outflow and short-axis transgastric (SAX TG) views were available in 90% (122/135) and 56% (76/135) of subjects, respectively. From the SAX TG view, coaptation gap measured 8.2±3.4 and 5.2±2.4 mm in the central and mid regions of the anterior-septal (AS) coaptation line, and 6.5±3.0 and 3.7±2.0 mm in the central and mid regions of the septal-posterior (SP) coaptation line (Figure 1). Coaptation gap measured 4.7±2.4, 5.2±2.4 and 4.6±3.0 mm in the anterior, mid and posterior aspects of the RV inflow/outflow view. The largest coaptation gap presented in the AS region in 79% (95/120) of subjects. A comparison of baseline characteristics, procedural strategy and outcomes stratified by location of the largest coaptation gap is provided in Table 1. Annulus and right ventricle size and presence of pacemakers were similar between groups. Torrential TR at baseline was more common in the SP group. Clipping strategy was similar with the majority of implants placed in the AS region. Implant success and acute procedural success (APS) were achieved in the majority of patients in both groups, with the SP group showing higher APS rates, 96% vs 85%, respectively. At 30-day follow-up, subjects with the largest gap in the SP region experienced more TR reduction at 30-day follow-up, 2.8±1.6 vs 2.1±1.3 grade reduction, respectively. Clinical improvements were observed in both groups: KCCQ increased by more than 15 points on average and the majority of subjects in both groups were NYHA I/II at 30-day follow-up. Conclusion: Coaptation gap size varies across the tricuspid valve and measurements at the intended clipping location should be taken into account when determining appropriateness of a given anatomy for tricuspid TEER. TriClip TEER offered high rates of implant and procedural success and improved clinical outcomes regardless of coaptation gap location. Subjects with SP coaptation gap localization are infrequent but should not be excluded from TEER therapy. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott